Intrusion prevention and active response deploying network and host IPS - Rash, Michael (Michael Brandon) (Rockland, MA : Syngress ; [Sebastopol] : Distributed by O'Reilly Media in the United States and Canada, 2005)
This book provides an introduction to the field of Intrusion Prevention and provides detailed information on various IPS methods and technologies. Specific methods are covered in depth, including both network and host IPS and response technologies such as port deactivation, firewall/router network layer ACL modification, session sniping, outright application layer data modification, system call interception, and application shims. * Corporate spending for Intrusion Prevention systems increased dramatically by 11% in the last quarter of 2004 alone * Lead author, Michael Rash, is well respected in the IPS Community, having authored FWSnort, which greatly enhances the intrusion prevention capabilities of the market-leading Snort IDS.
Intrusion prevention and active response -- Packet inspection for intrusion analysis -- False positives and real damage -- Four layers of IPS actions -- Network inline data modification -- Protecting your host through the operating system -- IPS at the application layer -- Deploying open source IPS solutions -- IPS evasion techniques (network).
Includes index.
Keywords: Computer networks -- Security measures; Computer network protocols; Computers -- Access control; Data protection; Electronic books